The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s12070-016-1035-8
|View full text |Cite
|
Sign up to set email alerts
|

Phonatory Symptoms and Acoustic Findings in Patients with Asthma: A Cross-Sectional Controlled Study

Abstract: To investigate the prevalence of phonatory symptoms, perceptual, acoustic and aerodynamic findings in patients with asthma compared to a control group. This study is a cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…In addition, we showed that pVHI scores were correlated positively with AR severity [19]. Previous studies with adult participants have shown that dysphonia was significantly more prevalent in patients with asthma compared to healthy participitans [5,16,17]. Restricted expiration, decreased lung volume, diaphragm, together with fluctuations in intra-thoracic and intra-abdominal pressures might hypothetically explain the significantly higher prevalence of voice disorders in patients with asthma.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…In addition, we showed that pVHI scores were correlated positively with AR severity [19]. Previous studies with adult participants have shown that dysphonia was significantly more prevalent in patients with asthma compared to healthy participitans [5,16,17]. Restricted expiration, decreased lung volume, diaphragm, together with fluctuations in intra-thoracic and intra-abdominal pressures might hypothetically explain the significantly higher prevalence of voice disorders in patients with asthma.…”
Section: Discussionmentioning
confidence: 49%
“…Restricted expiration, decreased lung volume, diaphragm, together with fluctuations in intra-thoracic and intra-abdominal pressures might hypothetically explain the significantly higher prevalence of voice disorders in patients with asthma. Additionally, mucosal changes due to obstructive respiratory disease, accompanying rhinosinusitis, the influence of laryngopharyngeal reflux and side effects of the inhaled corticosteroids may be responsible for the voice disorders [5,6,16]. To the best of our knowledge, this is the first study to examine the subjective evaluation of children with asthma using p-VHI and to compare the results with healthy controls.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…16 The results of this study conflict with the study done by Abdul et al which indicated no significant differences in MPD value in normal and asthma patient. 17 Also the result of this study indicated that experimental group had to put more effort to phonate compared to normal group. The prevalence of reduced phonation time in asthma and tuberculosis group can be explained on several bases: one is impaired expiration in both asthma and tuberculosis and also the restricted breathing which affects the phonation.…”
Section: Discussionmentioning
confidence: 69%